Impact of thyrotropin levels on outcomes in T1N0M0 papillary thyroid cancer after microwave ablation - Ying Wei; Zhen-Long Zhao; Jie Wu; Shi-Liang Cao; Na Yu; Li-Li Peng; Yan Li; Ming-An Yu (International Journal of Hyperthermia)
Objective To evaluate the impact of thyroid-stimulating hormone (TSH) levels on tumor progression and survival in patients with uni- and multifocal T1N0M0 papillary thyroid cancer (PTC) treated with microwave ablation (MWA).Methods This retrospective study analyzed the records of 525 patients with uni- and multifocal T1N0M0 PTC who underwent MWA from January 2015 to December 2022. Patients were stratified into uni-focal (U-PTC) and multifocal (M-PTC) groups and further categorized based on post-ablation TSH levels into low (≤1 mU/L), medium (1–2 mU/L), and high (>2 mU/L) subgroups. The tumor progression rates and progression-free survival were assessed.Results In U-PTC patients, lower TSH levels were significantly associated with higher tumor progression rates (10.1%) compared to those in the medium (2.9%) and high (2.1%) TSH groups (p = .009). Conversely, in M-PTC patients, tumor progression rates did not vary significantly across TSH levels. Progression-free survival rates in U-PTC patients were notably lower at the 5-year mark in the low TSH group (85.7%) compared to the medium TSH group (96.5%, p = .046). However, progression-free survival rates in M-PTC patients showed convergence across all TSH levels by the 5-year follow-up.Conclusion Maintaining TSH levels within the normal range post-ablation may be appropriate for managing T1N0M0 PTC treated with MWA, but randomized controlled trials are needed to confirm optimal TSH targets and their impact on outcomes.